The Effect of The Implementation of International Maritime Law and The Quality of Ship Crew on The Prevention of Coastal Environmental Pollution with Ship Safety as a Mediation in The Bintan Island Area - Andriyan Hendry Ole; Akbar Alim; Bambang Sumali; Marihot Simanjuntak; April Gunawan Malau (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
: This study aims to investigate the effect of the implementation of international maritime law and the quality of ship crews on the prevention of coastal environmental pollution with ship safety as a mediating variable in the Bintan Island area. With a focus on the issues of the implementation of maritime regulations that are not yet optimal and the variability of the quality of ship crews, this study uses a quantitative descriptive method approach with a sample of 160 ship crews in Bintan Island. The standard theory in takingThe samples used in this study were obtained using the Nonprobability Sampling technique with Saturated Sampling. Data were collected through a questionnaire that measured the variables of the application of international maritime law, the quality of the ship's crew, ship safety, and prevention of coastal environmental pollution. Data analysis was carried out using Structural Equation Modeling Partial Least Squares (SEM-PLS) to evaluate the relationship between variables. The results of the study indicate that the application of international maritime law has a significant effect on ship safety and prevention of coastal environmental pollution. In addition, the quality of the ship's crew also affects ship safety and pollution prevention efforts. Ship safety has been shown to play a significant role as a mediator in the relationship between the application of international maritime law andquality of ship crews with prevention of coastal environmental pollution. The discussion of these findings indicates that increasing the implementation of international maritime law and improving the quality of ship crews can improve ship safety and reduce environmental pollution. Ship safety plays a crucial role in mediating this relationship. This study concludes that stricter policies and effective training for ship crews will contribute to the protection of the coastal environment in Bintan Island. The implications of these results emphasize the importance of implementing better maritime policies and improving the competence of ship crews to achieve optimal results in preventing coastal environmental pollution.